2008
DOI: 10.1016/j.chembiol.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Binding Architecture of Human CB2 Cannabinoid Receptor: Evidence for Receptor Subtype-Specific Binding Motif and Modeling GPCR Activation

Abstract: SUMMARY The extensive physiological influence of transmission through the CB2 cannabinoid receptor makes this G protein-coupled receptor (GPCR) a promising therapeutic target for treating neuropathic pain, inflammation, and immune disorders. However, there is little direct structural information pertaining to either GPCR or CB2-receptor ligand recognition and activation. The present work helps characterize experimentally the ligand-binding interactions of the human CB2 (hCB2) receptor. This study illustrates h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
173
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(181 citation statements)
references
References 59 publications
8
173
0
Order By: Relevance
“…These studies have shown that the C-3 side chain of classical cannabinoids is aligned parallel with the membrane acyl chains (60,62) and that the fatty acid chain of endogenous cannabinoids orients parallel to membrane acyl chains with terminal methyl near the center of the bilayer (61). Cannabinoid ligand entry at the TMH6/7 interface is supported by isothiocyanate labeling studies of CB2 using the classical cannabinoid, AM841 functionalized at the C-3 dimethylheptyl side chain terminal carbon (1). Despite the fact that C7.42(288) faces into the CB2 binding pocket and would be a likely covalent attachment site if the ligand entered the CB2 binding pocket in the traditional way (from extracellular), AM841 was found to selectively label only one Cys residue, C6.47(257) (1).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…These studies have shown that the C-3 side chain of classical cannabinoids is aligned parallel with the membrane acyl chains (60,62) and that the fatty acid chain of endogenous cannabinoids orients parallel to membrane acyl chains with terminal methyl near the center of the bilayer (61). Cannabinoid ligand entry at the TMH6/7 interface is supported by isothiocyanate labeling studies of CB2 using the classical cannabinoid, AM841 functionalized at the C-3 dimethylheptyl side chain terminal carbon (1). Despite the fact that C7.42(288) faces into the CB2 binding pocket and would be a likely covalent attachment site if the ligand entered the CB2 binding pocket in the traditional way (from extracellular), AM841 was found to selectively label only one Cys residue, C6.47(257) (1).…”
Section: Discussionmentioning
confidence: 65%
“…A discussion of these differences as well as model construction details are provided in our recent paper (33). The resulting model has been tested via mutation (34), substituted cysteine accessibility (33, 35), and isothiocyanate labeling studies (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, rhodopsin/opsin have been reported to have lipid portals that are used for entry and exit via the lipid bilayer for 11-cis-retinal/trans-retinal as they are shuttled into and out of the receptor (Hildebrand et al, 2009). There is evidence from simulations (Hurst et al, 2010) and from experimental covalent labeling studies (Picone et al, 2005;Pei et al, 2008) that the cannabinoid receptors also possess a portal between transmembrane helix (TMH) 6 and TMH7 through which ligands enter. 3) In addition, the cannabinoid receptors and rhodopsin share an unusual GWNC amino acid sequence motif at the extracellular end of TMH4.…”
Section: Cb 1 Inverse Agonist Ldk1229mentioning
confidence: 99%
“…The 3D structures of CB1 and CB2 have also been modeled using Rhodopsin as template. (Pei, Y., Mercier, R. W., Anday, J. K., Thakur, G. A., Zvonok, A. M., Hurst, D. et al 2008) Another GPCR which has been characterized by homology modeling techniques was melatonin receptor. This receptor is responsible for the effects of melatonin, a compound taking part in resynchronization of biological rhythms such as sleep.…”
Section: Homology Modeling Studies Of Gpcrsmentioning
confidence: 99%